The Chicago handbook for teachers : a practical guide to the college classroom / Alan Brinkley,...[et al.] - Brinkley, AlanAuthor
The Chicago Handbook for Teachers is an extraordinarily helpful guide for all those who face the challenge of putting together material for a course and then making it work. Representing teachers at all stages of their careers, the authors, including distinguished historian Alan Brinkley, offer practical advice for almost any situation a new teacher might face, from preparing a syllabus to managing classroom dynamics. Beginning with a nuts and bolts plan for designing a course, the handbook also explains how to lead a discussion, evaluate your own teaching, deliver an effective lecture, supervise students' writing and research, create and grade exams, and more. Other sections address the less straightforward aspects of teaching, such as dealing with "diversity issues" and knowing where to draw the line in relationships with students. Particularly timely is an up-to-date discussion of when and how best to incorporate the Internet and other electronic resources into your teaching